KEMAMPUAN VISUAL SPASIAL SISWA DALAM MENYELESAIKAN SOAL PISA KONTEN SHAPE AND SPACE BERDASARKAN GAYA BELAJAR - Isnaini, Nur eni (Kadikma, 2020)
This study aims to describe students' spatial-visual ability in solving PISA questions in shape and space content based on visual, auditory, and kinesthetic learning styles. This type of research used in this research is descriptive qualitative research. Subjects in the study were six students from Class X MIPA 3 SMA Negeri 2 Tanggul consisting of two students from each of the visual, auditory and kinesthetic learning styles. The data collection methods used were questionnaires, tests, and interviews. The instruments used in this study were learning style questionnaires, shape and space content PISA test questions, and interview guidelines. The results showed that the achievement of the characteristics of the sixth spatial-visual abilities of the subjects differed. Students with a visual learning style can meet the characteristics of pattern search, conceptualization, problem-solving, and imagination in full. Students with an auditory learning style can meet the characteristics of conceptualization, problem-solving, and imagination completely but are unable to meet the characteristics of pattern search. Students with kinesthetic learning styles meet the characteristics of problem solving and imagination but are unable to meet indicators on the characteristics of pattern search and conceptualization. This can be seen from the results of solving the questions given and interviews conducted on the research subjects. Keyword: Spatial-Visual Ability, PISA Questions on Shape and Space Content, Learning Style